Novel and multiple targets for chimeric antigen receptor-based therapies in lymphoma - Pang, Yifan; Ghosh, Nilanjan (Frontiers in Oncology, 2024)
Chimeric antigen receptor (CAR) T-cell therapy targeting CD19 in B-cell non-Hodgkin lymphoma (NHL) validates the utility of CAR-based therapy for lymphomatous malignancies. Despite the success, treatment failure due to CD19 antigen loss, mutation, or down-regulation remains the main obstacle to cure. On-target, off-tumor effect of CD19-CAR T leads to side effects such as prolonged B-cell aplasia, limiting the application of therapy in indolent diseases such as chronic lymphocytic leukemia (CLL). Alternative CAR targets and multi-specific CAR are potential solutions to improving cellular therapy outcomes in B-NHL. For Hodgkin lymphoma and T-cell lymphoma, several cell surface antigens have been studied as CAR targets, some of which already showed promising results in clinical trials. Some antigens are expressed by different lymphomas and could be used for designing tumor-agnostic CAR. Here, we reviewed the antigens that have been studied for novel CAR-based therapies, as well as CARs designed to target two or more antigens in the treatment of lymphoma.